Comparing expectations and experiences of post-college transitions for higher vocational education and training (HVET) students in Xi’an after the covid-19 pandemic - Liu, Zihao (2025)
China’s Higher Vocational Education and Training (HVET) sector has experienced rapid expansion, yet remains overshadowed by entrenched cultural prejudices, structural barriers such as the hukou system, and persistent labour-market biases that devalue vocational qualifications. The HVET students’ post-college transition has become more complicated and high-risk under these circumstances compared to the past. More importantly, Covid-19 pandemic deteriorated these circumstances even further. Set against this fraught backdrop, the present study offers a student-centred examination of how HVET learners in Xi’an navigate their post-college transitions, whether through immediate employment or by ‘upgrading’ into bachelor’s programmes. The central aim is to identify how these learners form their expectations, why many fall short of their initial hopes, and which core factors, both systemic and individual, they perceive as most pivotal in shaping their transitions. By highlighting the social, economic, and cultural contexts surrounding these students, this research aims to dispel deficit-based narratives and illuminate the complex web of constraints and aspirations that shape their trajectories.